Evergreen: The First U.S. Veterans' Blind Rehabilitation Center. (March 2019) - Goodrich, Gregory L.; Zampieri, Tom
Evergreen was a World War I (WWI) adult, inpatient vocational rehabilitation facility for war-blind soldiers, sailors, and marines in the United States. Although Evergreen shared similarities with European war-blind rehabilitation organizations, it was novel in its philosophy and approach. It was also unlike any civilian blind rehabilitation program of its day. Although there are no comprehensive records known to us of how many troops became blind or sustained vision loss during WWI, studying published reports of the veterans served by Evergreen provides some insight into this population. As the United States' only blind rehabilitation facility for adults, Evergreen achieved several firsts, including having a national scope, being racially integrated (at least to some degree), and innovating a residential family training program. A role model of its day, it is now largely a footnote in the history of blind rehabilitation. We argue that the story of Evergreen contains lessons that should be remembered.